Trump's Energy Strategy: A Game-Changer for Global Oil Prices and Azerbaijan's Economy? - Gubad Ibadoghlu (ZBW - Leibniz Information Centre for Economics, 2025)
Azerbaijan, heavily dependent on oil and gas exports, faces significant economic challenges due to fluctuations in global energy markets, declining oil revenues, rising imports, and increasing fiscal instability. This paper examines the potential impact of the Trump administration's energy policies on global oil prices and their broader implications for Azerbaijan's economy. While deregulation and expanded fossil fuel production in the U.S. could drive oil prices down, geopolitical uncertainties surrounding Russia, Iran, and Venezuela may offset these effects. Additionally, U.S. alignment with Saudi Arabia and OPEC+ members, combined with capital discipline in the energy sector, may constrain the anticipated increase in production. Given these dynamics, Azerbaijan must urgently implement policy reforms and economic diversification strategies to mitigate potential risks and ensure long-term financial stability.
Keywords: 330; Trump Energy Policy; Oil Prices; Azerbaijan Economy; National Energy Emergency Act; U.S. Oil Production; Global Energy Market; Fossil Fuels; Geopolitical Risks; Oil and Gas Revenues; Economic Diversification